Species composition, diversity and traditional uses of plants in homegardens in Kampung Masjid Ijok, Perak, Malaysia - Mohd Raznan Ramli; POZI MILOW; SORAYYA MALEK (Society for Indonesian Biodiversity, 2021)
Abstract. Ramli MR, Milow P, Malek S. 2021. Species composition, diversity and traditional uses of plants in homegardens in Kampung Masjid Ijok, Perak, Malaysia. Biodiversitas 22: 1902-1911. The aim of present study was to analyze the status, plant diversity and their utilization in homegardens of Kampung Masjid Ijok, Perak, Malaysia. Forty homegardens were selected for detailed study: 9 were large (>1,500m2), 11 medium (901m2 to 1500m2) and 20 small (<900m2). A total of 207 plant species belonging to 78 families were recorded. Among the usable components, food plants dominated the homegardens with a proportion of 43.3% followed by ornamental (27.8% ) and medicinal (24%) plants. Large homegardens were dominated by food, medicinal and ornamental plant species, medium homegardens food and medicinal plant species, and small homegardens ornamental plant species. Frequency of species occurrences increased with the increasing homegardens size. The highest Shannon-Weiner Index was recorded in the large sized homegardens (3.61) and the lowest one in the small-sized homegardens (1.66). Euphorbiaceae (13 species), Araceae (11 species) and Fabaceae (10 species) were the most represented plant families. Shrubs dominated the plants in all homegardens with a proportion of 42 %, followed by trees (29.5%), herbs (23.7%) and climbers (4.8%). Musa paradisiaca L. was recorded as a very frequent species, followed by Cocos nucifera L., Nephelium lappaceum L., Capsicum frutescens L., Carica papaya L, Cymbopogon citratus (DC.) Stapf, Mangifera indica L, Curcuma domestica Valeton, Garcinia mangostana L and Manihot esculenta Crantz. Alocasia sanderiana and Aquilaria malaccensis categorized as critically endangered (CR) in (IUCN) Red List were also recorded in the large homegardens. This study suggested that large homegardens are more effective than the small and medium ones for diversification and conservation of plant species.